Beyond the slave narrative - Jenson, Deborah (Liverpool University Press, 2011)
This is an introduction to the Afro-diasporic literature of the Haitian revolution. It frames the unique contributions to anti-colonial thought of Haitian general Jean-Jacques Dessalines and other singular Haitian voices.
10.5949/UPO9781846316517
Keywords: Dessalines; Jean-Jacques; Toussaint Louverture; François Dominique; Literatur; Politik; Revolution; Kreolisch-Französisch; Haitian poetry (French Creole)